Circulating-free DNA: A promising tool for early detection of myocardial infarction - Sajjad Rafiei, MD; Amir Modarresi Chahardehi; Vuanghao Lim (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Myocardial infarction (MI) is a leading global cause of mortality, necessitating novel biomarkers for early diagnosis and prognosis. This review explores circulating cell-free DNA (cfDNA) as a minimally invasive tool for MI detection, focusing on its mechanistic role, diagnostic accuracy, and potential in personalized medicine. CfDNA levels rise rapidly post-ischemic event, correlating with myocardial damage and complementing troponins. Liquid biopsies using cfDNA enable dynamic monitoring of disease progression, but methodological variability and low concentrations limit its standalone use. Standardizing protocols and integrating cfDNA into multi-marker panels could enhance its clinical utility, positioning it as a transformative cardiovascular diagnostic tool.